Desulfovibrio vulgaris exacerbates sepsis by inducing inflammation and oxidative stress in multiple organs - Wu, Rong; Yu, Zhichao; Guo, Peiheng; Xiang, Xiaopeng; Zeng, Yunong; Fu, Shanshan; Yang, Mei; Huang, Xintao; Wang, Ze; Chen, Ali; Ge, Yuewei; Zhao, Xiaoshan; et al. (Frontiers in Microbiology, 2025)
IntroductionSepsis is a life-threatening condition that often leads to organ dysfunction and systemic inflammation, with gut microbiota dysbiosis playing a crucial role in its pathogenesis. The role of Desulfovibrio vulgaris (D. vulgaris), a potentially pathogenic bacterium, in sepsis remains unclear.MethodsWe first assessed the abundance of D. vulgaris in the feces of septic mice and patients using qPCR. Mice were then orally gavaged with D. vulgaris (2 × 108 CFU/mouse/day) for 7 consecutive days followed by cecal ligation and puncture (CLP) surgery. We monitored survival, assessed organ damage, and measured inflammation. Peritoneal macrophages were isolated to analyze the phosphorylation of key MAPK and NF-κB signaling pathways. Finally, oxidative stress levels in the liver, lungs, and kidneys were evaluated, measuring markers such as GSH, CAT, and SOD.ResultsThe abundance of D. vulgaris was significantly increased in the feces of both septic mice and patients. Supplementation with D. vulgaris exacerbated sepsis in mice, resulting in lower survival rates, more severe organ damage, and heightened inflammation. Phosphorylation of MAPK and NF-κB pathways in peritoneal macrophages was significantly enhanced. Additionally, D. vulgaris amplified oxidative stress across multiple organs, as indicated by increased ROS levels and decreased antioxidant enzyme activity.ConclusionOur findings suggest that D. vulgaris exacerbates the progression of sepsis by enhancing inflammation, activating key immune signaling pathways, and increasing oxidative stress. These processes contribute to organ dysfunction and increased mortality, highlighting the potential pathogenic role of D. vulgaris in sepsis.